A European Approach to Irritable Bowel Syndrome Management - Michel Delvaux; Jacques Frexinos (Canadian Journal of Gastroenterology)
Irritable bowel syndrome (IBS) is characterized by a number of clinical features and probably comprises a cluster of different conditions. The most frequent symptom reported by IBS patients is abdominal pain, although for a number of patients, bowel disturbances are the most prominent symptoms. Diarrhetic patients are seen in referral centres in continental Europe less frequently than in the United Kingdom or the United States. On the contrary, patients with constipation-prone IBS may comprise up to 80% of the IBS population referred to these centres. The pathophysiology of IBS is based on multiple factors. Most of the therapeutics proposed for the management of patients with IBS have been developed on the assumption that motility disorders of the gut are the most reliable pathological findings among these patients. Consequently, antispasmodics and motility regulatory agents have been widely used, alone or in association with intestinal adsorbents (clay-derived preparations), and laxatives or antidiarrhetic agents. Most of these drugs were developed several decades ago, and studies showing their efficacy have not reached the level of quality that is now required of randomized controlled trials. Therefore, following a complete and detailed review published in 1989, these drugs have not been used extensively in the United Kingdom or the United States. Large inquiries have also shown that the duration of prescription is quite different among countries. In European countries, maintenance therapy is frequently prescribed for several weeks to attempt to decrease the number of acute episodes. In contrast, psychotropic drugs are less popular among European gastroenterologists than among American gastroenterologists. However, multidisciplinary approaches to the treatment of these patients are frequent, and such drugs are often prescribed by home physicians. The results of large surveys estimated the yearly cost of such treatments to be around US$850. Patients with constipation and elderly patients with chronic disease receive more expensive treatments.